Biophysical Analysis of Bacterial CTP Synthase Filaments Formed in the Presence of the Chemotherapeutic Metabolite Gemcitabine-5′-triphosphate. Issue 8 (13th April 2018) - McCluskey, Gregory D.; Bearne, Stephen L.
Abstract: While enzyme activity is often regulated by a combination of substrate/effector availability and quaternary structure, many cytosolic enzymes may be further regulated through oligomerization into filaments. Cytidine-5′-triphosphate (CTP) synthase (CTPS) forms such filaments—a process that is promoted by the product CTP. The CTP analog and active chemotherapeutic metabolite gemcitabine-5′-triphosphate (dF-dCTP) is a potent inhibitor of CTPS; however, its effect on the enzyme's ability to form filaments is unknown. Alongside electron microscopy studies, dynamic light scattering showed that dF-dCTP induces Escherichia coli CTPS ( Ec CTPS) to form filaments in solution with lengths ≥ 30 nm in the presence of CTP or dF-dCTP. The substrate UTP blocks formation of filaments and effects their disassembly. Ec CTPS variants were constructed to investigate the role of CTP-binding determinants in CTP- and dF-dCTP-dependent filament formation. Substitution of Glu 149 (i.e., E149D), which interacts with the ribose of CTP, caused reduced affinity for both CTP and dF-dCTP, and obviated filament formation. Phe 227 appears to interact with CTP through an edge-on interaction with the cytosine ring, yet the F227A and F227L variants bound CTP and dF-dCTP. F227A Ec CTPS did not form filaments, while F227L Ec CTPS formed shorter filaments in the presence of CTP or dF-dCTP. Hence, Phe 227 plays a role in filament formation, although replacement by a bulky hydrophobic amino acid is sufficient for limited filament formation. That dF-dCTP can induce filament formation highlights the fact that nucleotide analogs employed as chemotherapeutic agents may affect the filamentous states of enzymes and potentially alter their regulation in vivo . Graphical abstract: Highlights: Gemcitabine-5′-triphosphate (dF-dCTP) promotes filament formation by CTP synthase. In the presence of CTP and dF-dCTP, 28- and 53-nm filaments were detected by DLS. UTP inhibits dF-dCTP-induced filament formation and effects filament disassembly. Interaction of Glu 149 with CTP and dF-dCTP is required for filament formation. A bulky hydrophobic group at residue 227 is sufficient for filament formation.